IMPROVING STUDENTS’ LISTENING ABILITY AT ELEVENTH GRADE IN SMA NEGERI 4 PEMATANGSIANTAR THROUGH AUDITORY, INTELLECTUALLY, AND REPETITION (AIR) MODEL - Juni Sari Sianturi; Selviana Napitupulu (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2025)
Listening is one of the essential skills in English language learning; however, manystudents still face difficulties in comprehending spoken texts, particularly in distinguishing thepronunciation of regular past tense verbs ending in –ed (/t/, /d/, and /ɪd/). This study aimed toexamine the effectiveness of the Auditory, Intellectually, and Repetition (AIR) learning modelin improving students’ listening ability at the eleventh grade of SMA Negeri 4 Pematangsiantar.This research employed a quantitative approach using a quasi-experimental design. Theparticipants consisted of 72 eleventh-grade students divided into an experimental group (XI-8)and a control group (XI-7). Data were collected through pre-test and post-test listeningassessments and analyzed using descriptive statistics and inferential analysis. The findingsrevealed that the experimental group showed a significant improvement in listeningperformance, with the mean score increasing from 52.77 in the pre-test to 77.36 in the post-test.Meanwhile, the control group experienced only a slight improvement. The results indicate thatthe AIR learning model is effective in enhancing students’ listening comprehension, particularlyin recognizing the pronunciation of regular past tense verbs ending in –ed. Therefore, the AIRmodel can be considered an effective alternative strategy for teaching listening in senior highschools.Keywords: Listening ability, AIR learning model, Pronunciation, Regular past tense verbs,Quasi-experimental study.